A point prevalence cross-sectional study of healthcare-associated urinary tract infections in six Australian hospitals. Issue 7 (29th July 2014) - Gardner, Anne; Mitchell, Brett; Beckingham, Wendy; Fasugba, Oyebola
Abstract : Objectives: Urinary tract infections (UTIs) account for over 30% of healthcare-associated infections. The aim of this study was to determine healthcare-associated UTI (HAUTI) and catheter-associated UTI (CAUTI) point prevalence in six Australian hospitals to inform a national point prevalence process and compare two internationally accepted HAUTI definitions. We also described the level and comprehensiveness of clinical record documentation, microbiology laboratory and coding data at identifying HAUTIs and CAUTIs. Setting: Data were collected from three public and three private Australian hospitals over the first 6 months of 2013. Participants: A total of 1109 patients were surveyed. Records of patients of all ages, hospitalised on the day of the point prevalence at the study sites, were eligible for inclusion. Outpatients, patients in adult mental health units, patients categorised as maintenance care type (ie, patients waiting to be transferred to a long-term care facility) and those in the emergency department during the duration of the survey were excluded. Outcome measures: The primary outcome measures were the HAUTI and CAUTI point prevalence. Results: Overall HAUTI and CAUTI prevalence was 1.4% (15/1109) and 0.9% (10/1109), respectively. Staphylococcus aureus and Candida species were the most common pathogens. One-quarter (26.3%) of patients had a urinary catheter and fewer than half had appropriate documentation. Eight of the 15 patients ascertained to have a HAUTI based on clinical records (6 being CAUTI) were coded by the medical records department with an International Classification of Diseases (ICD)-10 code for UTI diagnosis. The Health Protection Agency Surveillance definition had a positive predictive value of 91.67% (CI 64.61 to 98.51) compared against the Centers for Disease Control and Prevention definition. Conclusions: These study results provide a foundation for a national Australian point prevalence study and inform the development and implementation of targeted healthcare-associated infection surveillance more broadly.